Analisis Profitabilitas dan Efisiensi Biaya pada Usaha Rujak Cireng sebagai Produk Kuliner UMKM - Mohammad Afrizal Miradji; Bayuadi Bayuadi; Rahmi Tara Iman Aisyah; Putri Mariana; Tri Aji Pratomo; Nabila Mar’Atus Sholichah (Journal of Economics, Management, and Accounting, 2025)
This study aims to analyze the profitability and cost efficiency of rujak cireng as a micro, small, and medium enterprise (MSME) culinary product with market potential among students, university students, and the general public. The main issue addressed is the extent to which rujak cireng can generate optimal profits with limited capital and how production cost management supports business sustainability. A qualitative descriptive approach was employed, with data collected through direct observation of the production process, detailed recording of raw material, energy, packaging, and distribution costs, as well as daily sales simulations. Financial data were analyzed to calculate net profit, profit margin, and cost efficiency to assess the business’s financial feasibility. The results indicate that with a capital of IDR 765,000, the rujak cireng business can achieve daily revenue of IDR 2,000,000 and a net profit of IDR 1,235,000, yielding a profit margin of 61.75%. A simple cost structure, the use of local raw materials, and optimized home-based production processes contribute to high cost efficiency. These findings confirm that rujak cireng is a viable and profitable MSME culinary venture with long-term growth potential, providing significant economic benefits for both entrepreneurs and the surrounding community.